Clinical and mutational spectrum of Charcot–Marie–Tooth disease type 2Z caused by MORC2 variants in Japan. (3rd August 2017) - Ando, M.; Okamoto, Y.; Yoshimura, A.; Yuan, J.‐H.; Hiramatsu, Y.; Higuchi, Y.; Hashiguchi, A.; Mitsui, J.; Ishiura, H.; Fukumura, S.; Matsushima, M.; Ochi, N.; et al.
Abstract : Background and purpose: The microrchidia family CW‐type zinc finger 2 gene ( MORC2 ) was newly identified as a causative gene of Charcot–Marie–Tooth disease (CMT) type 2Z in 2016. We aimed to describe the clinical and mutational spectrum of patients with CMT harboring MORC2 mutations in Japan. Methods: We analyzed samples from 781 unrelated patients clinically diagnosed with CMT using deoxyribonucleic acid microarray or targeted resequencing by next‐generation sequencing, and samples from 434 mutation‐negative patients were subjected to whole‐exome sequencing. We extracted MORC2 variants from these whole‐exome sequencing data and classified them according to American College of Medical Genetics standards and guidelines. Results: We identified MORC2 variants in 13 patients. As the second most common causative gene of CMT type 2 after MFN 2, MORC2 variants were detected in 2.7% of patients with CMT type 2. The mean age of onset was 10.3 ± 8.7 years, and the inheritance pattern was mostly sporadic (11/13 patients, 84.6%). The clinical phenotype was typically length‐dependent polyneuropathy, and electrophysiological studies revealed sensory‐dominant axonal neuropathy. Mental retardation was identified in 4/13 patients (30.8%). p.Arg190Trp, as a mutational hotspot, was observed in eight unrelated families. We also identified two novel probably pathogenic variants, p.Cys345Tyr and p.Ala369Val, and one novel uncertain significance variant, p.Tyr332Cys. Conclusions: Our study is the largest report of patients harboring MORC2 variants. We revealed a clinical and mutational spectrum of Japanese patients with MORC2 variants. More attention should be paid to cognitive impairment, and the responsible mechanism requires further research for elucidation.